Determination of yeast killer activity in fermenting sugarcane juice using selected ethanol-making strains - Ceccato-Antonini,Sandra Regina (2004)
Twenty-four yeasts out of 342 isolated from the fermentative process showed killer activity and three of them were selected for the fermentative efficiency evaluation in batch system with cell recycle, flask and fermentor experiments. The selected three killer strains did not present similar results to those of pressed (baking) yeast concerning ethanol (0.07-0.18; 0.12-0.20; 0.10-0.13; 0.22-0.25 g/g, respectively) and biomass (0.19-0.26; 0.33-0.39; 0.13-0.27; 0.47-0.61 g/g, respectively) yields and fermentative efficiency (12.3-36.3; 21.0-40.0; 19.3-26.3; 47.6-54.0 %, respectively) in sugarcane juice, in flasks. In fermentor, similar behaviour was observed. However, the selected strains showed high cellular viability and killer activity (using cell-free filtrate) along the fermentative cycles, in spite of the unfavourable conditions of the medium, like high pH variation of the medium (from 5.5-6.0 to 3.0-4.0), low aeration and higher temperature (30º C), which were not the ideal ones for the production/activity of killer toxins. A Pichia strain (CCA 510) showed the best results among the killer yeasts tested, exhibiting a killer activity against 92% of isolated fermentative yeasts of the process and against the pressed (baking) ferment. It also demonstrated killer activity (using crude toxin preparation) at higher temperatures (38ºC) and low pH (4.0) after 72 hours of incubation, under proliferative and non-proliferative conditions. The results indicated that the killer activity should be a characteristic to be looked for in the strain selection for ethanolic fermentation, beside other important productivity-based characteristics, since it assure the permanence of the selected strain during the process.